Euglycemic Ketoacidosis in a Patient with Metastatic Non-Small-Cell Lung Adenocarcinoma and Concomitant Pulmonary Embolism - Robert Sean O’Neill; Lauren Tyack; Mary Freeman; Hussein Soudy Hussein (Case Reports in Endocrinology, 2020)
Euglycemic ketoacidosis is a recognised side effect secondary to sodium-glucose cotransporter 2 inhibitor use in the treatment of type 2 diabetes mellitus; however, there is scarce evidence to suggest whether preexisting comorbid conditions contribute to the development of this potentially life-threatening complication. We describe a case of euglycemic ketoacidosis in a patient with type 2 diabetes mellitus in the context of empagliflozin use after a recent diagnosis of metastatic lung adenocarcinoma. The diagnosis was complicated by a pulmonary embolism and hospital-acquired pneumonia, and was subsequently established after an anion-gap metabolic acidosis was identified on arterial blood gas and serum ketone measurement. The patient required admission to the intensive care unit for fluid resuscitation and regular intravenous insulin to ensure resolution of acidosis and maintenance of normoglycaemia. The patient was discharged to home for outpatient single-agent pembrolizumab for treatment of his lung adenocarcinoma. This article highlights the importance or awareness of oral hypoglycaemic medications and their side effects, along with providing further evidence for the potential contribution of malignancy to the development of euglycemic ketoacidosis in a patient with type 2 diabetes mellitus.